Pegylation: an overview and recent advances reported in the patent literature - Gonzalez, Marianela (2011)
Pegylation technologies have improved since chemistry and purification processes have advanced over the years. Furthermore, a gradual better understanding of the clinical responses has spurred the need for more effective therapeutic agents. Nowadays, it is necessary to early identify therapy needs and technical capabilities to develop customized, innovative products that reach the market successfully. Consequently, the main technical efforts are directed to solve some intricate problems associated with the drug delivery where improved solubility, in vivo stability, targeted delivery, and enhanced efficacy and safety are the major challenges. Too many alternative approaches for too many needs open up the possibility for follow-on developers and competitors, and provide opportunities for innovation that provoke an intense worldwide competition in a complex intellectual property environment. This paper presents an overview of general trends and patents supporting PEGylation platforms. Since the golden rule is that PEGylation has to be tailored to each specific drug and application, the review format is structured by specific conjugated species alphabetically sorted within the following groups: PEG-protein conjugates, PEG-antibody and antibody fragment conjugates, PEG-oligonucleotide conjugates, PEG-small molecule drug conjugates, and PEGylated materials and miscellaneous applications.